Pengaruh Bauran Pemasaran Ritel Terhadap Keputusan Pelanggan Membeli Buku (Studi Kasus Pada Toko Buku Toga Mas Denpasar) - hartini, ni made (E-Jurnal Manajemen, 2013)
Diskon Book Store Toga Mas Denpasar as a retailer sells as books obtain from the publicher to distribute these product to end consumers. The purpose of this study was to determine the influence of retail mix in customer decision to buy book on Diskon Book Store Toga Mas Denpasar. The populations in this study were identified as customer of Diskon Toga Mas Denpasar. Sampling method used is type of purposive sampling. Determination of sample size of using Slovin formula, so that a proper sample is taken is 100 . The analytical method used is Regression Factor Analysis. The results has been obtained that the product/merchandise, price, promotion, location, atmosphere, and retail services partially and simultaneously positive and significant to customer  decision to buy book on The Diskon Book Store Toga Mas Denpasar. The location factors more dominant influence on customer  decision to buy book. Managerial implications that can be raised from the results of this research is management The Diskon Book Store Toga Mas Denpasar should focus on location, retail service, price, product/merchandise, atmosphere, and promotion in developing their businesses to achieve influence customer purchasing decision. The result is expected to be used as a basis for further research to determine consumer purchasing decision whit other retail stores as book stores. Key Words : Retail Marketing Mix, Purchasing Decision